The Effectiveness of Educational Games in Understanding Learning English for Kindergarten Students Bunga Bangsa School, Indonesia - Candra, Kiki Irafa; Leonia, Rizqy Aisyah; Suyantri, Eni (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2024)
Education to children is very instrumental for understanding future learning, to be able to provide understanding for children must be with a fun learning model with games. This study aims to see the effectiveness of educational games Word Scavenger Hunt on the understanding of English learning at Bunga Bangsa Kindergarten, this study uses quasi-experimental methodology with a control group and an experimental group. In addition, the students of Bunga Bangsa Kindergarten gave positive reactions to the educational games used in learning because the educational games made the learning process more fun, exciting and by incorporating educational games into English learning is an effective approach to improve learning outcomes. In addition, the media can stimulate students' desire and enthusiasm to learn English in the long run. So in conclusion, Bunga Bangsa Kindergarten students understand English learning more easily through the Word Scavenger Hunt educational game than only with the Conventional learning model.